Prevalence and types of sexual inactivity in Britain: analyses of national cross-sectional probability survey data - Catherine H Mercer; Peter Ueda (BMJ Open)
Objectives To examine how prevalence and context of sexual inactivity varies across the life-course, assess dissatisfaction with sex life among those who are sexually inactive and identify associations with factors that may represent reasons for sexual inactivity.Design Analysis of cross-sectional probability sample survey data.Setting British general population.Participants 14 623 participants (n men: 6045 unweighted, 7245 weighted), aged 16–74 years, of the third National Survey of Sexual Attitudes and Lifestyles (Natsal-3), undertaken in 2010–2012.Main outcome measures Sexual inactivity, defined as not reporting oral, vaginal or anal intercourse in the past year and further categorised into those who were sexually inexperienced (had never had sex), single or in a relationship.Results Overall, 15.9% (weighted n 1155/7245) of men and 22.2% (1646/7410) of women were sexually inactive (p<0.001). The proportion of sexually inactive individuals who were sexually inexperienced was larger among men than women (26.3% (304/1155) vs 16.3% (268/1646)), while the proportion who were singles was larger among women (49.8% (820/1646) vs 40.4% (467/1155)). Sexual inexperience was the most common type of sexual inactivity in early adulthood, with this declining with age. A minority of those who had sexual experience but were sexually inactive—34.8% (293/842) of men and 23.6% (319/1349) of women—reported being dissatisfied with their sex lives. Associations with sexual inactivity was observed for a range of sociodemographics and sexual behaviours/attitudes, for example, religion, ethnicity, Body mass index, height, employment status and index of multiple deprivation; these associations varied by type of sexual inactivity and gender.Conclusions While sex is important for well-being, a non-negligible proportion of the population at all ages are sexually inactive, yet many are not dissatisfied with their situation, with implications for sex and relationship counselling.